2014
DOI: 10.11648/j.plant.20140203.11
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis of Nigerian and Egyptian Henna (Lawsonia Inermis L.) Leaves using TLC, FTIR and GCMS

Abstract: Abstract:This study designed to compare phytochemicals for both Nigerian and Egyptian henna using preliminary test for secondary metabolites, thin layer chromatography (TLC), Fourier Transform Infrared spectroscopy (FTIR), and Gas Chromatography Mass spectroscopy (GCMS). Lawsonia inermis L. (Lythraceae) commonly called henna known for its cosmetic properties. The active ingredients in the leaves were extracted and fractionated using chloroform, ether, methanol, and ethyl-acetate. The resultant fractions primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 6 publications
0
5
0
2
Order By: Relevance
“…A prior study revealed the existence of several chemicals that were extracted from henna plants in Egypt and Nigeria using various solutions, including methanol and chloroform. Resins, glycosides, flavonoids, sterols, and other substances were discovered in this study [ 49 ]. The presence of 1,4-naphthalenedione,2-hydroxy (19.…”
Section: Resultsmentioning
confidence: 99%
“…A prior study revealed the existence of several chemicals that were extracted from henna plants in Egypt and Nigeria using various solutions, including methanol and chloroform. Resins, glycosides, flavonoids, sterols, and other substances were discovered in this study [ 49 ]. The presence of 1,4-naphthalenedione,2-hydroxy (19.…”
Section: Resultsmentioning
confidence: 99%
“…Isolation, identification of the various phytoconstituents from the Rostellularia diffusa and the Henna leaves (Lawsonia inermis L.) has been for carried out further research sourcing the pharmaceutical significance [7][8] . The same type of work was also carried out from Pistia stratiotes L., Eichhornia crassipes (Mart) with various solvents and showed different types of low molecular compounds by GCMS, from the root nodules of Vigna mungo L [9][10] and And rographis paniculata [11],from this study unknown bioactive compounds have been identified qualitatively by using the method [12 ] .Phytochemical constituents in Curcuma Caesia Roxb (Black Turmeric) extracted with methanol and identified using GSMS and FTIR which revealed the presences of tannins, terpenoids, flavonoids, alkaloid, phenol phytosterol qoinones and saponins and observed Curcuma Caesia Roxb as an herbal alternative for various disease [13]. Medicinal roles of tannins, flavonoids, saponins and steroids extracted with methanol from Carissa spinarum have been identified using GCMSto understand the role of the plant as a medicine [14].…”
Section: Introductionmentioning
confidence: 93%
“…In Yazd, Iran, and many other places, henna leaves were ground into powder using henna millstones that were driven by powerful men, camels, and other animals. These henna millstones are made of limestone and have grooves cut into their surfaces to make grinding easier (127). Henna is produced commercially on a large scale for industrial uses in many nations, including India, Pakistan, Bangladesh, and Sudan.…”
Section: Processing and Preparation Of Hennamentioning
confidence: 99%